2011
DOI: 10.1080/00981389.2010.527570
|View full text |Cite
|
Sign up to set email alerts
|

Elder Abuse and Neglect in a Population Offering Care by a Primary Health Care Center in Izmir, Turkey

Abstract: The objective of this study is to investigate the prevalence of abuse and neglect of the elderly aged 65 years and older, living with their relative in a primary health care center area and affecting factors. A descriptive study included 331 people aged 65 years. The most frequent type of abuse was psychological abuse and the least frequent was sexual abuse. Female gender, low education levels, living with spouses and children, and perception of familial relationships as average or below average significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 27 publications
2
39
2
2
Order By: Relevance
“…The study by Kissal and Beser in Turkey in 2011 showed that the most common type of elder abuse was psychological abuse (16).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Kissal and Beser in Turkey in 2011 showed that the most common type of elder abuse was psychological abuse (16).…”
Section: Discussionmentioning
confidence: 99%
“…National data on elder abuse in Turkey does not exist, although there have been a few regional studies with small samples . Two studies involved elderly persons living in their own homes in western Turkey and found the prevalence of abuse to be 13.3–14.2% .…”
Section: Introductionmentioning
confidence: 99%
“…Significant levels of elderly mistreatment have been identified in nations across Asia [10-13]. A study from Chennai (N = 400) found 14% prevalence of elderly mistreatment, where chronic verbal abuse was the most common followed by financial abuse, physical mistreatment, neglect and injuries from burns [14].…”
Section: Introductionmentioning
confidence: 99%